Membangun Kreativitas: Pelatihan Desain Grafis untuk Siswa SMA 1 Kaway XVI - Sempena, Iwan Doa; Amri, Saiful; Nuril Fahdi, Nuril; Husna, Asmaul; Putri, Noni; Mawaddarahmah, Mawaddarahmah; Jamalia, Jamalia; Purnawan, Sastra; Wardani, Zakiatul; Maulina, Maulina; lovita, Fantia; Ikbal, Muhamad (Lok Seva: Journal of Contemporary Community Service, 2025)
A graphic design training using Adobe Photoshop was conducted to enhance the visual design skills of students at SMA 1 Kaway XVI. The purpose of this program was to introduce fundamental design concepts and provide practical experience for students who had limited or no experience. Prior exposure to designing software. The methodology involved observation, pre-test and post-test assessments, and hands-on practice in creating promotional posters using Adobe Photoshop. A total of 20 students participated and demonstrated significant improvement in their design abilities. The evaluation results revealed increased understanding of design elements such as typography, color, and visual composition. Moreover, the training encouraged students to be more creative and confident in expressing their ideas visually. The outcomes of this initiative are not only applicable in an academic context but also broaden the students’ entrepreneurial perspective in the creative industry. This training proves that a practical, technology-based approach can serve as an effective solution in developing students’ technical skills in the digital era.